Volume 2A: Advanced Manufacturing 2014
DOI: 10.1115/imece2014-38228
|View full text |Cite
|
Sign up to set email alerts
|

Geometry Assurance Integrating Process Variation With Simulation of Spring-In for Composite Parts and Assemblies

Abstract: Geometrical variation and deviation in all manufacturing processes affect quality of the final product. Therefore geometry assurance is an important tool in the design phase of a new product. In the automotive and aviation industries where the use of composite parts is increasing drastically, new tools within variation simulations are needed. Composite parts tend to deviate more from nominal specification compared to metal parts. Methods to simulate the manufacturing process of composites have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…high quality requirements, to avoid aesthetical defects or internal residual stresses. Moreover, small geometrical deviations on product single components involve significant geometrical deviations on the entire assembly, as studied in these works, 1,2 that may be in composite or in composite and metallic materials. 3 Geometrical deviations are generally caused by residual stress and deformations due to the cure process and to the thermo-mechanical characteristics of the involved materials.…”
Section: Introductionmentioning
confidence: 95%
“…high quality requirements, to avoid aesthetical defects or internal residual stresses. Moreover, small geometrical deviations on product single components involve significant geometrical deviations on the entire assembly, as studied in these works, 1,2 that may be in composite or in composite and metallic materials. 3 Geometrical deviations are generally caused by residual stress and deformations due to the cure process and to the thermo-mechanical characteristics of the involved materials.…”
Section: Introductionmentioning
confidence: 95%
“…Polini et al 16 reported their tolerance analysis study of a composite flaperon involving free-form surfaces. Jareteg 1,17 and S€ oderberg et al 18 studied composite assembly tolerance analysis and variation simulation. Wang and Li 19,20 proposed a preloading modified probability density function based tolerance simulation method for the composite wingbox assembly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…11 The uncertainty in ply thickness and fiber orientations of polymer matrix composite materials and the spring-in phenomena due to the curing process was studied in Ref. 12 Some works of the literature combined the spring-in deviations of L-shaped parts into a T-shaped assembly in polymer matrix reinforced by fibers through the method of influence coefficients [13][14][15][16] or by means of finite element analysis (FEA). 17 It can be underlined that there is no work of the literature on the management of the entire information flow from manufacturing to assembly.…”
Section: Introductionmentioning
confidence: 99%
“…11 The uncertainty in ply thickness and fiber orientations of polymer matrix composite materials and the spring-in phenomena due to the curing process was studied in Ref. 12…”
Section: Introductionmentioning
confidence: 99%